Opposing Roles for the Related ETS-Family Transcription Factors Spi-B and Spi-C in Regulating B Cell Differentiation and Function - Laramée, Anne-Sophie; Raczkowski, Hannah; Shao, Peng; Batista, Carolina; Shukla, Devanshi; Xu, Li; Haeryfar, S. M. Mansour; Tesfagiorgis, Yodit; Kerfoot, Steven; DeKoter, Rodney (Frontiers in Immunology, 2020)
Generation of specific antibodies during an immune response to infection or vaccination depends on the ability to rapidly and accurately select clones of antibody-secreting B lymphocytes for expansion. Antigen-specific B cell clones undergo the cell fate decision to differentiate into antibody-secreting plasma cells, memory B cells, or germinal center B cells. The E26-transformation-specific (ETS) transcription factors Spi-B and Spi-C are important regulators of B cell development and function. Spi-B is expressed throughout B cell development and is downregulated upon plasma cell differentiation. Spi-C is highly related to Spi-B and has similar DNA-binding specificity. Heterozygosity for Spic rescues B cell development and B cell proliferation defects observed in Spi-B knockout mice. In this study, we show that heterozygosity for Spic rescued defective secondary antibody responses in Spib-/- mice. Plasma cell differentiation was accelerated in Spib-/- B cells. Gene expression, ChIP-seq, and reporter gene analysis showed that Spi-B and Spi-C differentially regulated Bach2, encoding a key regulator of plasma cell and memory B cell differentiation. These results suggest that Spi-B and Spi-C oppose the function of one another to regulate B cell differentiation and function.